NOISE-INDUCED HEARING LOSS IN OIL FIELDS - Abdulelah, Haider; Badr, Sanaa Q.; Alaziz, Baheya Abdulbaqi (International Journal Multidisciplinary (IJMI), 2026)
Objective: Noise-induced hearing loss (NIHL) poses a significant risk to workers in high-noise environments, particularly in the oil industry. This study investigates the prevalence of NIHL and tinnitus among employees at Basra Oil Company. Method: Recent data indicates that 23% of workers exposed to noise experience hearing loss, compared to only 7% among those not exposed, and a preliminary assessment of hearing difficulty was conducted, revealing critical risk factors such as increased noise exposure and family history of hearing issues. Pure-tone audiometry (PTA) testing, performed on 354 workers, found that none showed significant hearing impairment, suggesting effective safety measures. Result: However, the gradual nature of NIHL necessitates ongoing monitoring and preventive strategies. Novelty: Recommendations include implementing regular hearing tests every six months, establishing comprehensive hearing conservation programs, and promoting awareness of noise hazards, with these measures aiming to safeguard the auditory health of workers and improve overall occupational safety.